TECHNOLOGY-BASED LEARNING IN MADRASAH: FACING THE CHALLENGES OF THE DIGITAL AGE - Loso Judijanto; Syafril Barus; Mahidin Fahmie (CV. ADIBA AISHA AMIRA, 2025)
The digital era has brought various innovations in all aspects of life, including in the world of education. The integration of technology in the learning system in madrasah is a necessity that cannot be ignored to prepare students to face future challenges. This paper explores how madrasahs can implement technology in the teaching and learning process, ranging from the use of hardware and software, online learning platforms, to educational applications. The research method used is literature review. The results show the importance of technology integration in learning in madrasahs to improve the quality of education and prepare students adequately for the digital era. Despite the challenges, collaboration among education stakeholders is considered crucial in ensuring a successful transition to a technology-based learning system, which in turn will shape a more innovative, interactive learning environment that supports students' overall development